Integration of Artificial Intelligence in Islamic Religious Learning - Muksin, Muksin; Musli, Musli; Della Amrina Yusra; Afandi, Afandi (Scidac Plus, 2026)
This study aims to analyze how Artificial Intelligence (AI) can be integrated into Islamic education in a way that maintains a balance between technological innovation and the ethical-spiritual foundations of Islamic learning. The study addresses the challenge of utilizing AI-based technologies without compromising essential ethical considerations, such as data privacy, algorithmic bias, and the potential misinterpretation of religious texts. These concerns highlight the need for a thoughtful and ethically grounded approach to technological adoption in Islamic educational contexts. This research employs a qualitative design using semi-structured interviews, document analysis, and a systematic literature review to examine current perspectives and practices regarding AI integration in Islamic education. The data are analyzed through thematic analysis to identify patterns related to pedagogical benefits, ethical challenges, and institutional readiness. The findings indicate that AI has considerable potential to support personalized learning, improve teaching efficiency, and expand access to educational resources. However, its successful integration requires a robust ethical framework grounded in Islamic values. The study emphasizes the importance of teacher training that promotes ethical literacy and critical technological engagement. Collaboration among educators, Islamic scholars, policymakers, and technology developers is essential to ensure that AI strengthens, rather than undermines, the moral and spiritual objectives of Islamic education.